ANALISIS PERENCANAAN STRATEGIS SISTEM INFORMASI DAN KOMUNIKASI PADA SD NEGERI REUDEUP - Yusransal Yusransal; Mulya Arifah; Agustina Agustina; Mufti Mufti; Iis Marsithah; Sri Milfayetty (Jurnal Guru Kita PGSD, 2022)
Abstract: Analysis of Information and Communication System Strategic Planning at SD Negeri Reudeup. SDN Reudeup is one of the state formal education institutions in Meureubo District, West Aceh Regency. In managing school operations, SDN Reudeup has implemented an information system. However, the information system used has not had a significant influence on the achievement of optimal competitive competition. This is because the application of information systems has not been used as a strategic tool but only supports the process of processing school administrative data. For this reason, SDN Reudeup requires a strategic planning of information systems in order to compete competitively with other schools. The framework used in this research is the Ward & Peppard framework. The Ward & Peppard framework begins with an understanding of the current situation, namely the internal and external environment, both in the business environment and in the IS/IT environment. The data analysis methods used are Value Chain analysis, SWOT analysis, PEST analysis and McFarland Strategic Grid. The process of collecting data was carried out by interview techniques, namely by conducting personal interviews (personal interviews), observations with a structured observation approach and documentation studies. The purpose of this research is to make strategic planning of information systems at SDN Reudeup to increase competitive advantage in schools.